THEORIZING THE CONCEPT OF TRANSFORMATIVE LEARNING EXPERIENCE IN THE CONTEXT OF TEACHER PROFESSIONAL DEVELOPMENT - Goba, Līva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The concept of learning experience holds its eminent place within the paradigm of constructivism in contemporary educational science. The study process is being designed and construed to foster educative experiences in accordance with the desired learning outcomes. Transformative learning theory and the concept of perspective transformation marks a specific type of learning experience – one that reconstructs the frame of reference of the learner. Such a paradigmatic shift is also considered necessary for large-scale educational reforms to succeed. Transformative learning theory itself doesn’t provide clear-cut solutions for implementation of a certain reform ideology, to the contrary – it questions the assumptions that guide one’s action in order to construct a more inclusive, better informed and functional meaning perspective which may disagree with the assumptions that are imposed institutionally. As part of teacher professional development, transformative learning practices hold a promise for emancipation of the teaching profession and the development of agency. This article theorizes the concept of learning experience from the perspective of phenomenology and the theory of transformative learning, bringing forward the concept of transformative learning experience. The aim of the research is to explore the concept of transformative learning experience as an object of study within teacher professional development.